Rewelacyjny wieczór piosenki, humoru, parodii. (Słupsk : [s.n.], 1946)
Afisz inform. o wieczorze 27.08.1946 r.
Keywords: Brzezińska, Hanna -- (1909-1998).; Życie artystyczne -- Polska -- Słupsk -- 1945-1970.; Słupsk (Polska) -- 1945-1970 -- druki ulotne